2020
DOI: 10.1007/s11033-020-05958-7
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of interferon-alpha gene in bovine embryos produced in vitro in response to experimental infection with noncytophatic bovine-viral-diarrhea virus

Abstract: In-vitro fertilization is a routine livestock-breeding technique widely used around the world. Several studies have reported the interaction of bovine viral-diarrhea virus (BVDV) with gametes and in-vitro-produced (IVP) bovine embryos. Since, gene expression in BVDV-infected IVP bovine embryos is scarcely addressed. The aim of this work was to evaluate the differential expression of genes involved in immune and inflammatory response. Groups of 20-25 embryos on Day 6 (morula stage) were exposed (infected) or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The study suggested a role for the suppressed innate and adaptive immune responses in the developing lymphoid organs in the persistence of the BVDV in the PI animals and, on the other hand, a role for the upregulation of the innate immune response genes in transiently infected fetuses in virus clearance from these animals (127). Bovine embryonic cells showed the ability to take the function of immune cells by recognizing and responding to BVDV infection through the upregulation of genes encoding for INFα and TLR7, which are involved in inflammatory and immune responses (128).…”
Section: Bvdv-induced Immune Response and Immune Dysfunctionmentioning
confidence: 99%
“…The study suggested a role for the suppressed innate and adaptive immune responses in the developing lymphoid organs in the persistence of the BVDV in the PI animals and, on the other hand, a role for the upregulation of the innate immune response genes in transiently infected fetuses in virus clearance from these animals (127). Bovine embryonic cells showed the ability to take the function of immune cells by recognizing and responding to BVDV infection through the upregulation of genes encoding for INFα and TLR7, which are involved in inflammatory and immune responses (128).…”
Section: Bvdv-induced Immune Response and Immune Dysfunctionmentioning
confidence: 99%